IMPLEMENTASI LABORATORIUM VIRTUAL MENGGUNAKAN MODEL EVALUASI CIPP - Yuyun Suprapto; Bambang Bagus Hariyanto; Moch. Rifai; Achmad Setiyo Prabowo (Politeknik Penerbangan Surabaya, 2023)
During the COVID-19 pandemic, the teaching and learning process, especially in practical courses that were originally face-to-face, turned to online. This change has had several impacts on lectures, especially in learning outcomes and the quality of graduates in terms of skills. Therefore, it is very necessary to conduct an evaluation in this learning process using the CIPP model developed by Stufflebeam. This evaluation model aims to find out how effective the use of virtual laboratories in daring practical courses is. This research is an evaluative research that uses a qualitative descriptive approach. Where the data used in this study is qualitative data with analytical methods. The technique used in this research is to examine the existing data using grounded research methods. From the results of this study, the largest percentage is that the use of virtual laboratories has been quite effective in daring learning during the covid 19 pandemic, with the improvement and development of media and learning models that are more innovative and creative. In addition, efforts in skills that directly deal with equipment directly still need to be fulfilled in real laboratories in order to increase enrichment and deeper understanding and skills in work procedures in the world of work later.